2022
DOI: 10.1134/s1070363222020050
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of Novel Hydrazone and 1,2,4-Triazole-3-thione Derivatives

Abstract: Novel hydrazone and 1,2,4-triazole-3-thione derivatives were obtained via the reaction of N1,N3,2-triaryl-6-hydroxy-6-methyl-4-oxocyclohexane-1,3-dicarboxamides with acid hydrazides and thiosemicarbazide, respectively. Structure of the products was proved using IR and 1H NMR spectroscopy methods. Some of the synthesized compounds were tested for antimicrobial activity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…1,2,4-triazole-3-thione (TZT) derivatives: TZT was identified as a potential motif that interacted with the two zinc ions of MBL (L1) through one of the three nitrogen atoms, and sulfur atom, at the same time. An initial crystal structure evaluation of the analogous compound in complex with the L1 enzyme [132] led to synthesis [133][134][135][136][137][138][139][140] (Scheme 36) and enzymatic inhibition studies on a variety of compounds with variable substituents at positions 4 and 5 of TZT. A number of selected compounds exhibited IC 50 values in the micro-molar range against representative MBLs (i.e., L1, VIM-4, VIM-2, NDM-1, and IMP-1 and CphA); however, limited success was observed in the microbiological assays [134][135][136][137]139,140].…”
Section: 24-triazole-3-thione (Tzt) Derivativesmentioning
confidence: 99%
“…1,2,4-triazole-3-thione (TZT) derivatives: TZT was identified as a potential motif that interacted with the two zinc ions of MBL (L1) through one of the three nitrogen atoms, and sulfur atom, at the same time. An initial crystal structure evaluation of the analogous compound in complex with the L1 enzyme [132] led to synthesis [133][134][135][136][137][138][139][140] (Scheme 36) and enzymatic inhibition studies on a variety of compounds with variable substituents at positions 4 and 5 of TZT. A number of selected compounds exhibited IC 50 values in the micro-molar range against representative MBLs (i.e., L1, VIM-4, VIM-2, NDM-1, and IMP-1 and CphA); however, limited success was observed in the microbiological assays [134][135][136][137]139,140].…”
Section: 24-triazole-3-thione (Tzt) Derivativesmentioning
confidence: 99%
“…They have shown promising potential in the development of antimicrobial and anticancer drugs. Numerous studies have demonstrated the potent antimicrobial activity of hydrazone‐based compounds against various bacterial and fungal pathogens [8–12] . Additionally, hydrazone derivatives have represented promising anticancer activity by inhibiting cancer cell proliferation and inducing apoptosis [13–19] .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the potent antimicrobial activity of hydrazone-based compounds against various bacterial and fungal pathogens. [8][9][10][11][12] Additionally, hydrazone derivatives have represented promising anticancer activity by inhibiting cancer cell proliferation and inducing apoptosis. [13][14][15][16][17][18][19] The mechanism of action of these compounds involves targeting specific cellular pathways and enzymes, facilitated by their multiple hydrogen bond acceptor/donor atoms that can interact with biological targets.…”
Section: Introductionmentioning
confidence: 99%